Two-dimensional beam focusing impact localization based on probabilistic tomography fusion. (1st September 2022) - Chang, Qi; Zhao, Heng
Highlights: A two-dimensional beam-focusing (TDBF) theory is proposed to increase the accuracy and minimize the blind zone of impact localization. The velocity of acoustic emission signal excited by impact and propagated in plate structure is measured and described as probability distribution. With the TDBF localization algorithm the impact localization result can be displayed with probabilistic tomography which is more precise and intuitive than traditional deterministic description. The accuracy of the linear sensor array with one dimension beam focus algorithm according to the impact occurred at different angle is measured after multiple tests. To fuse the two tomography calculated using the longitudinal and horizontal sensor array, the Bayes fusion is adopted to fuse the tomography concerning the accuracy which can make the impact localization more precise and credible. Abstract: Monitoring structural impact is one of the main research aspects of structural health monitoring. A new algorithm for impact localization(IL) is proposed in this paper through a two-dimensional beam-focusing (TDBF) probabilistic tomography theory. The newly developed method is based on the arrangement of cross-shaped piezoelectric sensor (PZT) which has greatly improved the accuracy of IL. Moreover, in the proposed TDBF localization algorithm, the accuracy of the ultrasonic wave velocity achieved during testing has emerged as the main factor that ameliorates the IL. The probability distribution of the velocity is obtained through statistical analysis and introduced into the TDBF localization algorithm to localize the impact through probabilistic tomography. To further improve the accuracy of the IL, Bayes theory is also adopted to fuse two impact tomography obtained by horizontal sensor array and longitudinal sensor array, respectively. The effectiveness and credibility of the TDBF-IL are verified through comprehensive experimental research which indicate the promising prospects of proposed method in accurate and effective monitoring of structural health.